Bokashi And Botanical Pesticides Production Training in Support Organic Farming for Sustainable Agriculture - Wiyono; Budiyono, Agus; Supriyadi, Teguh; siti mardhika sari (Universitas Tunas Pembangunan Surakarta, 2024)
Agriculture is an important sector in maintaining food security in a country, including Indonesia. The practice of agricultural activities is very dependent on the environment. Environmentally friendly agricultural practices, also known as organic farming, are currently widely popular, public awareness of the quality of healthy food is the reason why organic farming practices are increasingly in demand. This agricultural practice is related to the recycling of nutrients through plant and livestock waste, as well as other waste which can improve the fertility status and structure of the soil. Community service activities are located in Dlingo Village, Mojosongo District, Boyolali, involving the Mudho Tani livestock group. The method used is providing material regarding the manufacture of organic fertilizer and vegetable pesticides by utilizing materials found in the environment. Organic fertilizer uses cow dung because the majority of the group members are livestock breeders, while vegetable pesticides use spices (ginger, turmeric, mackerel). The practice of making fertilizers and pesticides is carried out to increase the skills of farmers so that they can apply the principles of organic farming. With this service activity, it is hoped that farmers' skills in making organic fertilizers and pesticides can increase and can be applied to agricultural practices. The implementation of an organic farming system is one of the supports for creating a sustainable agriculture.